2019
DOI: 10.1158/1078-0432.ccr-19-0148
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Lymphocyte Heterogeneity in Advanced Cutaneous T-cell Lymphoma Skin Tumors

Abstract: Purpose: The heterogeneity of tumor cells presents a major challenge to cancer diagnosis and therapy. Cutaneous T-cell lymphomas (CTCL) are a group of T lymphocyte malignancies that primarily affect skin. Lack of highly specific markers for malignant lymphocytes prevents early diagnosis, while only limited treatment options are available for patients with advanced stage CTCL. Droplet-based single-cell transcriptome analysis of CTCL skin biopsies opens avenues for dissecting patient-specific T lymphocyte hetero… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
139
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(147 citation statements)
references
References 52 publications
(64 reference statements)
6
139
0
2
Order By: Relevance
“…It has recently been discovered by us and other groups that CTCL is heterogenous at transcriptomics and protein level. [45][46][47][48] Single cell approach would allow for precise mapping of malignant T-cell clones identified by a unique pair of rearranged TCRA and TCRB sequences to the mutational pattern and gene expression profiles. However, our results identified one potential problem in studies on ITH in multifocal tumor such as MF.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been discovered by us and other groups that CTCL is heterogenous at transcriptomics and protein level. [45][46][47][48] Single cell approach would allow for precise mapping of malignant T-cell clones identified by a unique pair of rearranged TCRA and TCRB sequences to the mutational pattern and gene expression profiles. However, our results identified one potential problem in studies on ITH in multifocal tumor such as MF.…”
Section: Discussionmentioning
confidence: 99%
“…Although this technology is still relatively contained within the research space, clinical applications using this technology will likely advance patient care in the next decade. Single cell sequencing studies have shown evidence of tumor heterogeneity in CTCLs and there is also preliminary evidence that there may be a prognostic impact (45)(46)(47). Demonstration of specific gene expression profiles enabling examination of the tumor microenvironment along with the tumor cells in the same assay provides useful insights to tumor biology and immune response, which ultimately helps in tailoring personalized treatments, understanding prognosis, response to therapy, and reasons for drug resistance (48,49).…”
Section: Single Cell Sequencingmentioning
confidence: 99%
“…Many CTCL's had differential expression of genes that was unique to that tumor signifying its importance in personalizing patient specific therapy. A common gene expression profile of highly proliferating lymphocytes was identified which was present in all tumors indicating its potential diagnostic role (47).…”
Section: Single Cell Sequencingmentioning
confidence: 99%
“…Polo-like kinase4 (PLK4) is a serine/threonine kinase crucial for mitosis and DNA integrity and has emerged as a therapeutic target for the treatment of multiple cancers 29,30 . The serum and glucocorticoidregulated kinase 1 (SGK1) and the receptor of the G-protein signaling 1 (RGS1) are reportedly upregulated in CTCL, as determined using genome wide and single cell analyses 31,32 . The principal component analysis of full transcriptomes in this study revealed a high degree of individual variation in gene expression ( Figure 5e, j).…”
Section: Detailed Characterization Of Gene Expression In Malignant Tmentioning
confidence: 99%